Spinoza's ethics:a reader's guide - "Cook, J.Thomas" (New York, 2008)
"The Ethics" is one of the undisputed masterworks of early modern philosophy. In this single volume Spinoza offers the reader an unorthodox account of God, a novel version of the mind-body relation, a systematic theory of the emotions and a detailed prescription for human virtue and blessedness. Too controversial to be published during his lifetime, it was surreptitiously printed by Spinoza's friends after his death. Nowadays the Ethics is studied in university classes as an exemplary work of early modern rationalism. In "Spinoza's 'Ethics': A Reader's Guide", J. Thomas Cook explains the philosophical background against which the book was written and the key themes inherent in the text. The book then guides the reader to a clear understanding of the text as a whole, before exploring the reception and influence of this classic philosophical work. This is the ideal companion to study of this most influential and challenging of texts.
Keywords: Ethics